2017
DOI: 10.1136/bmjopen-2016-015467
|View full text |Cite
|
Sign up to set email alerts
|

International multiphase mixed methods study protocol to develop a cross-cultural patient-reported outcome instrument for children and young adults with cleft lip and/or palate (CLEFT-Q)

Abstract: IntroductionPatient-reported outcome (PRO) instruments should be developed according to rigorous guidelines in order to provide clinically meaningful, scientifically sound measurement. Understanding the methodology behind instrument development informs the selection of the most appropriate tool. This mixed methods protocol describes the development of an internationally applicable PRO instrument, the CLEFT-Q, for evaluating outcomes of treatment for cleft lip and/or palate (CL/P).Methods and analysisThe study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 32 publications
0
100
0
Order By: Relevance
“…Full protocol details have been published. 18 Content was developed from interviews with 138 patients from 6 countries. 19 Findings were used to develop a conceptual framework comprising 3 domains; i.e., appearance, health-related quality of life and facial function.…”
mentioning
confidence: 99%
“…Full protocol details have been published. 18 Content was developed from interviews with 138 patients from 6 countries. 19 Findings were used to develop a conceptual framework comprising 3 domains; i.e., appearance, health-related quality of life and facial function.…”
mentioning
confidence: 99%
“…We used a modern psychometric approach called Rasch Measurement Theory (RMT) . Figure shows our multiphase iterative mixed‐methods approach . This paper describes phases I and II.…”
Section: Methodsmentioning
confidence: 99%
“…Flow diagram showing the multiphase mixed‐methods protocol for developing the ACNE ‐Q (reproduced with permission from Wong Riff et al .) . QUAN , quantitative; QUAL , qualitative.…”
Section: Methodsmentioning
confidence: 99%
“…22 The definition of QoL used in these measures evolved through a phased approach, beginning with systematic review of extant literature and qualitative methods (including in-depth patient interviews) and progressing to development of scales, field testing, and psychometric validation and evaluation. 23,24 This approach has helped identify meaningful, replicable outcome measures, 22,23 and published minimum standards help promote appropriate uses of these PRO measures. 25 This approach has also been applied in developing and validating scales for a number of facial conditions, including the FACE-Q for aesthetic facial procedures 6,7,26 and the CLEFT-Q for cleft lip and palate.…”
Section: Developing a Standardized Instrument For Ftmentioning
confidence: 99%
“…25 This approach has also been applied in developing and validating scales for a number of facial conditions, including the FACE-Q for aesthetic facial procedures 6,7,26 and the CLEFT-Q for cleft lip and palate. 24 Some have suggested that the FACE-Q might eventually be adapted for use in FT, 27 but existing PRO measures, such as those used in FACE-Q, have not been validated in the FT population due in part to small numbers of FT candidates and recipients. Eventually, as more procedures are undertaken, PRO measures might be developed for FT. A standardized PRO instrument for FT would help support the procedure's eventual transition from research to standard of care and would help facilitate reimbursement by third-party payers.…”
Section: Developing a Standardized Instrument For Ftmentioning
confidence: 99%